"There's a huge benefit just to know that someone cares:" a qualitative examination of rural veterans' experiences with TelePain - Molly Silvestrini; Jess Indresano; Steven B. Zeliadt; Jessica A. Chen (BMC, 2021)
Abstract Background Veterans in the United States are at an increased risk of chronic pain and have higher reported pain prevalence and severity than nonveterans. This qualitative study aims to examine veterans' perspectives on the acceptability of receiving pain care through TelePain, a telehealth program implemented by the Veterans Health Administration (VA) that offers specialty pain care to rural veterans in their homes or in a video conferencing room at a nearby outpatient clinic. Methods The VA electronic health record was used to identify patients who were referred to TelePain from rural clinics located in Washington, Oregon, and Alaska between 12/01/2019 and 03/31/2020. The study team completed 16 semi-structured interviews with rural veterans about their experiences with TelePain. After interview transcripts were recorded digitally and transcribed, Atlas.ti was used to organize data and facilitate qualitative coding. Interview transcripts were analyzed using thematic analysis. Results Veterans reported general satisfaction with receiving pain care through telehealth and valued having supportive, knowledgeable providers who provided useful information and resources. In addition, veterans appreciated the convenience of telehealth. Barriers to care included problems with program follow-up, negative perceptions of mental health care for pain, and preference for in-person care. Although some patients suggested that telehealth audio and video could be improved, most patients did not have any significant problems with telehealth technology. Conclusions In this sample of rural veterans who used TelePain, many reported satisfaction with the program and positive experiences with providers. Targets for quality improvement include streamlining the program's referral and scheduling process and improving patient motivation to engage in psychological pain treatments. Results indicate that delivering pain services over telehealth is an acceptable modality for this patient population.